Intentions and Behavioural Determinants in the Face of covid-19 Pandemic - Sergio Barbosa; Camilo Andrés Ordóñez; Laura Andrea León; Andrés David Huerfia Coronado (Avances en Psicología Latinoamericana, 2023)
The containment of Covid 19 implies challenges for governments and health authorities to motivate citizens to adopt several prevention behaviours (i.e., wearing a face mask, washing hands frequently). The purpose of this paper is to identify the factors that motivate people to adopt these behaviours. Our analysis was conducted over data collected by ASCOFAPSI and the Universidad Autónoma de Barcelona about attitudes and beliefs related to the pandemic from 919 people from Colombia). The data was collected using a snowball online sampling between May and June 2020. We found that each prevention behaviour is motivated by a different set of factors. Specifically, based on the theory of planned behaviour, our results suggest that the intention to adopt a kind of preventive behaviour is predicted by a set of variables about subjective norms and attitudes as independent variables and a set of variables linked to perceived control as mediator variables. This suggests that the motivation of prevention behaviours from authorities should be particular to each kind of behaviour and consider the associated particular pattern of motivations as well as sociodemographic characteristics and possibilities of action.